Smart systems for capable users? Nurses’ experiences on patient information systems 2017 - Hyppönen, Hannele; Lääveri, Tinja; Hahtela, Nina; Suutarla, Anna; Sillanpää, Kirsi; Kinnunen, Ulla-Mari; Ahonen, Outi; Rajalahti, Elina; Kaipio, Johanna; Heponiemi, Tarja; Saranto, Kaija (Finnish Journal of eHealth and eWelfare, 2018)
Globally, there are only a few studies on healthcare professionals' experiences of their patient information systems, although user experiences are a key component of system development and assessment. A nationwide survey of nurses' experiences was conducted for the first time in Finland in early 2017. The survey was targeted to working-age nurses, community nurses and midwives from the Membership Registers of the Nursing Association and the Tehy. A similar study has been conducted for physicians in 2010, 2014 and 2017. An electronic questionnaire, based on the physicians’ questionnaire, was sent by the Nursing Association and Tehy to their members. A total of 3607 nurses responded to the questionnaire. The results were grouped using the objectives of the Finnish eHealth and eSocial 2020 Strategy theme "Smart Systems for Capable Users". Responses differed by patient information system brands and by the respondents' operating environments. One of the most prominent problems was the need to record the same thing in many places, which can expose to errors and indicates poor information system integration. Poor stability of information systems was also identified as a common problem; identified as a risk to patient safety in previous literature. There were differences between brands in usability of information systems and availability of up-to-date and high quality information in patient care locally, regionally and nationally. Respondents felt that in-service training was inadequate with regard to changes in operating methods required by information systems. Active user participation in the development of information systems was associated with better school grades given by the respondent for the information system. This will be studied in more detail in a separate article. Participation in the development of information systems and training take initially time from direct customer and patient work, but good usability and usage skills can later be expected to save time due to fluent use of information systems. The system and context specific differences in the information system usability and support to work as well as quality of care identified in this study can be used to pinpoint good design practices in different contexts of use. This is needed to improve efficiency of the nurses’ work and to increase patient safety and co-operation. Nurses need to be better consulted when developing information systems. Organizations need to design information system training so that the skills of the professionals remain up to date as information systems and their usage patterns evolve. The Nursing Association's e-Health Strategy also emphasizes the user eHealth competence and participation in development work.